Circular subsidiarity: Humanizing work through relational goods - González, Ana Marta; Scalzo, Germán (Wiley, 2024)
The Fourth Industrial Revolution based on digitalization, the development of AI, robotics, big data, and increasing automation is dredging up older debates on the end of human work. This article contributes to this debate arguing that these changing circumstances represent an opportunity to advance a renewed consideration of human work. By emphasizing its most distinctively human dimensions, including gratuitousness, relationality, and meaningfulness, we propose the articulation of a social model that recognizes relational goods as a specific contribution of human work in an attempt to overcome the state and the market's monopoly of public life built around the dichotomy between the private and the public. Such a social model is based on the concept of circular subsidiarity, which represents a departure from traditional notions of subsidiarity by promoting a dynamic and reciprocal interplay between three essential societal spheres: the state, the market, and organized civil society, all of which have their role to fulfill by providing security, efficiency, and relational goods. Ultimately, this article suggests that circular subsidiarity can lead to a more inclusive and equitable social model by acknowledging how relational goods not only humanize civil society but also sustain the functioning of both the market and the state. ©Wiley